Non-communicable diseases, especially Diabetes Mellitus, inUmrah/Hajj pilgrims: community prevention and management efforts - Heny Surya Widiyaningsih; Irfansyah Baharuddin Pakki; Yadi Yadi (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Non-communicable diseases (NCDs), especially Diabetes Mellitus (DM), pose a major health risk for Umrah and Hajj pilgrims. This population often comprises elderly individuals with pre-existing comorbidities. The physically demanding and crowded environment of pilgrimage increases the likelihood of severe complications, such as cardiovascular events and diabetic foot ulcers. Objective : This narrative review aims to synthesize evidence on the prevalence, contributing factors, and behavioral interventions addressing DM among pilgrims. Research Methods/ Implementation Methods : A synthesis of 34 articles published between 2010 and 2024 from PubMed and Google Scholar revealed that up to 58.2% of pilgrims have NCDs, with 87.9% categorized as high-risk. The primary determinants of morbidity and mortality include older age, hypertension, DM, and obesity. DM-related complications are frequent, with hypoglycemia reported in 37% of cases and foot wounds in 31%. Results : Interventions based on the Health Belief Model (HBM) effectively improved diabetes selfcare behaviors. Among HBM constructs, self-efficacy and perceived benefits were the strongest predictors of treatment adherence and proper disease management. Conclusion/Lesson Learned : NCDs remain a critical health concern among Umrah and Hajj pilgrims. Comprehensive screening and predictive models are essential to identify high-risk individuals before departure. In addition, structured behavioral education that enhances self-efficacy should be prioritized to strengthen chronic disease management throughout the pilgrimage.